Patrick J. Lucey : a lasting legacy - Dresang, Dennis L. (Wisconsin Historical Society Press, 2020)
"As Wisconsin governor from 1971 to 1977, Patrick J. Lucey pursued an unusually wide-ranging and ambitious progressive agenda, tempered by the concerns of a fiscal conservative and a pragmatic realist. He was known for bridging partisan divides, building coalitions, and keeping politics civil, even when dealing with his opponents. His legacy, which included merging Wisconsin's universities into one system and equalizing the funding formula for public schools, continues to impact Wisconsin residents and communities"-- Provided by publisher.
Keywords: Lucey, Patrick J., -- 1918-2014.; Lucey, Patrick J., -- 1918-2014; Governors -- Wisconsin -- Biography.; Wisconsin -- Politics and government -- 1951-; Gouverneurs -- Wisconsin -- Biographies.; Governors; Politics and government; Wisconsin; Since 1951; Biographies